Animal movements in fire‐prone landscapes. (18th December 2018) - Nimmo, Dale G.; Avitabile, Sarah; Banks, Sam C.; Bliege Bird, Rebecca; Callister, Kate; Clarke, Michael F.; Dickman, Chris R.; Doherty, Tim S.; Driscoll, Don A.; Greenville, Aaron C.; Haslem, Angie; Kelly, Luke T.; et al.
ABSTRACT: Movement is a trait of fundamental importance in ecosystems subject to frequent disturbances, such as fire‐prone ecosystems. Despite this, the role of movement in facilitating responses to fire has received little attention. Herein, we consider how animal movement interacts with fire history to shape species distributions. We consider how fire affects movement between habitat patches of differing fire histories that occur across a range of spatial and temporal scales, from daily foraging bouts to infrequent dispersal events, and annual migrations. We review animal movements in response to the immediate and abrupt impacts of fire, and the longer‐term successional changes that fires set in train. We discuss how the novel threats of altered fire regimes, landscape fragmentation, and invasive species result in suboptimal movements that drive populations downwards. We then outline the types of data needed to study animal movements in relation to fire and novel threats, to hasten the integration of movement ecology and fire ecology. We conclude by outlining a research agenda for the integration of movement ecology and fire ecology by identifying key research questions that emerge from our synthesis of animal movements in fire‐prone ecosystems.